The varieties of transcendence : pragmatism and the theory of religion - Deuser, Hermann, 1946- (American philosophy series (Unnumbered), 2016)
The anthology focuses on the major classical pragmatist theories of religion. It is unique in pointing out pragmatist concepts of religious individualization as alternatives to the common secularization discourse and by stressing the compatibility of religious individualism with a positive concept of community.